Carbon-carbon triple bond cleavage and reconstitution to achieve aryl amidation using nitrous acid esters - Zi-Ying Wang; Shoujun Wang; Nan-Nan Dai; Yao Xiao; Yu Zhou; Wen-Chan Tian; Dongru Sun; Qiang Li; Yong Wang; Wen-Ting Wei (Nature Communications)
Abstract C–C bond cleavage and recombination provide an efficient strategy for the modification and reconstruction of molecule structures. Herein, we present a method for achieving amidation of aryl C(sp2)–H bond through the cleavage and recombination of C–C triple bond with the involvement of nitrous acid esters. This method marks the instance of precise and controlled stepwise cleavage of C–C triple bond, offering a fresh perspective for the cleavage of such bonds. Nitrous acid ester serves as both a radical source and a hydrogen atom transfer (HAT) reagent to functionalize and utilize the two carbon atoms of the C–C triple bond. The alkoxy radical captures the hydrogen atom from the aryl C(sp2)–H bond or N-hydroxyl to induce the 1,3-oxygen radical migration, which is crucial for the subsequent cleavage of the C–C bond.